Composition for labels and application thereof
By applying an isolation coating composed of materials such as cellulose acetate and other materials on the back of the label, the problem of wrinkling and curling of hot melt adhesive labels during storage is solved, ensuring the smoothness of the label appearance and the improvement of the product image. .
Patent Information
- Application Number
- CN202411260905.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-10
AI Technical Summary
Hot melt adhesive labeling is prone to wrinkling and curling at the label sticker during storage, especially during high temperatures and long-term storage, which seriously affects the appearance of the product.
Coat a layer of isolation coating composed of cellulose acetate propionate, hydroxyacrylic resin, α-Al2O3 powder, mica tablet powder, latent crosslinking agent, stabilizer and wear-resistant agent on the back of the label, through gravure or difference The application of quick coating technology forms a barrier layer with structural rigidity and balanced stress to prevent direct contact between the hot melt adhesive and the label substrate.
Effectively prevent label wrinkling and curling, keep the label's appearance flat and beautiful, and enhance the product packaging image.
Smart Images

Figure CN119286322A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for a label, a coating formed by coating the composition, a method for preparing the coating, a label comprising the coating and a packaging material comprising the label. Background Art
[0002] Hot melt adhesive labeling is a very common form of labeling. The commonly used hot melt adhesives on the market are mainly rubber-based hot melt adhesives. After rubber-based hot melt adhesive labeling, the label will gradually wrinkle and warp to varying degrees after being placed for a period of time. This phenomenon is particularly serious on foamed pearlescent film labels, and the higher the storage temperature and the longer the storage time, the more obvious this phenomenon is, seriously affecting the appearance of the product. Summary of the invention
[0003] In view of the above problems, the present invention significantly improves the appearance of the label pasted with hot melt adhesive by coating a layer of isolation coating on the back of the label (i.e. between the hot melt adhesive and the label), thereby enhancing the appearance of the product.
[0004] The invention provides a composition for a label, which consists of cellulose acetate propionate, hydroxy acrylic resin, α-Al2O3 powder, mica flake powder, a latent crosslinking agent, a stabilizer, an anti-wear agent and a first solvent, wherein the stabilizer is anhydrous ethanol or isopropanol, the anti-wear agent is micro-powder polyethylene wax or micro-powder polytetrafluoroethylene wax or a mixture of the two, and the first solvent is ethyl acetate and / or n-propyl acetate.
[0005] In some embodiments, the anti-wear agent is micronized polyethylene wax.
[0006] In some embodiments, the composition consists of the following substances in terms of mass percentage:
[0007]
[0008] In some embodiments, the composition consists of the following substances in terms of mass percentage:
[0009]
[0010] In some embodiments, the composition consists of the following substances in terms of mass percentage:
[0011]
[0012] In some embodiments, the composition consists of the following substances in terms of mass percentage:
[0013]
[0014] In some embodiments, the composition is composed of the following substances by mass percentage:
[0015]
[0016]
[0017] In some embodiments, the latent cross-linking agent is selected from the group consisting of zirconate chelates, titanate chelates, and any combination thereof.
[0018] In some embodiments, the latent cross-linking agent is selected from zirconium bis(diethyl citrate) dipropoxide, titanium acetylacetonate, and any combination thereof.
[0019] In some embodiments, the stabilizer is isopropanol.
[0020] In some embodiments, the first solvent is a combination of ethyl acetate and n-propyl acetate. In some embodiments, the first solvent is a combination of ethyl acetate and n-propyl acetate, and the mass ratio of ethyl acetate to n-propyl acetate is (3-15):1. In some embodiments, the first solvent is a combination of ethyl acetate and n-propyl acetate, and the mass ratio of ethyl acetate to n-propyl acetate is (5-10):1. In some embodiments, the first solvent is a combination of ethyl acetate and n-propyl acetate, and the mass ratio of ethyl acetate to n-propyl acetate is (7.5-8):1.
[0021] In some embodiments, the α-Al2O3 powder is a powder of 500-600 mesh.
[0022] In some embodiments, the D50 particle size of the mica flakes is 2-8 microns, preferably 5 microns.
[0023] In some embodiments, the cellulose acetate propionate has an acetyl content of 0.1-5%, a propionyl content of 40-50%, and a hydroxyl content of 0-5%. In some embodiments, the cellulose acetate propionate has an acetyl content of about 2.5%, a propionyl content of about 45%, and a hydroxyl content of about 2.6%.
[0024] In some embodiments, the molecular weight of the hydroxylated acrylic resin is 20000-30000, for example, about 25000. In some embodiments, the hydroxyl value of the hydroxylated acrylic resin is 40-60 mg KOH / g. In some embodiments, the hydroxyl value of the hydroxylated acrylic resin is 40-47 mg KOH / g. In some embodiments, the hydroxyl value of the hydroxylated acrylic resin is 47-53 mg KOH / g. In some embodiments, the hydroxyl value of the hydroxylated acrylic resin is 53-60 mg KOH / g. In some embodiments, the hydroxyl value of the hydroxylated acrylic resin is about 56 mg KOH / g.
[0025] The present invention also provides a coating formed by coating the above composition.
[0026] The present invention also provides a method for preparing the coating as described above, comprising:
[0027] 1) diluting the composition as described above with a second solvent,
[0028] 2) applying the diluted composition onto a substrate by gravure coating or differential coating,
[0029] 3) Drying.
[0030] In some embodiments, the second solvent is ethyl acetate and / or n-propyl acetate. In some embodiments, the second solvent is ethyl acetate.
[0031] In some embodiments, after drying, the coating has a coating weight of 1.5-2.5 g / m 2 , for example about 1.6 g / m 2 , about 1.7g / m 2 , about 1.8g / m 2 , about 1.9g / m 2 , about 2.0g / m 2 , about 2.1g / m 2 , about 2.2g / m 2 , about 2.3g / m 2 , about 2.4g / m 2 .
[0032] In some embodiments, step 3) is dried at a temperature of 70-80° C. for 2-5 seconds.
[0033] The present invention also provides a label, comprising a label substrate, a printing layer located on the front side of the label substrate, and the above-mentioned coating layer located on the back side of the label substrate.
[0034] In some embodiments, the printing layer includes an ink printing layer and a varnish printing layer. The ink printing layer and the varnish printing layer can be printed on the label substrate with reference to the printing method disclosed in CN118126570A. Printing a varnish printing layer on the ink printing layer can protect the surface of the label, making the label more durable and wear-resistant, and can also present effects such as gloss, matte, touch, and pattern, so as to decorate the label.
[0035] In some embodiments, the label substrate is a pearlescent film. In some embodiments, the label substrate is a double-sided corona pearlescent film. In some embodiments, the label substrate is a film with a density of 0.65 to 0.8 g / cm 3 In some embodiments, the label substrate has a density of 0.65 to 0.8 g / cm 3 The double-sided corona pearlescent film has a corona value preferably greater than or equal to 38 dynes.
[0036] The present invention also provides a packaging material, which comprises a container and the label as described above, wherein the label is attached to the surface of the container by hot melt adhesive.
[0037] In some embodiments, the container is a bottle. In some embodiments, the container is made of one or more materials selected from high-density polyethylene, polyethylene terephthalate, and polypropylene.
[0038] In some embodiments, the hot melt adhesive is a rubber-based hot melt adhesive.
[0039] The present invention also provides a method for preparing the composition as described above, comprising:
[0040] 1) adding cellulose acetate propionate to a solvent to dissolve it;
[0041] 2) Add hydroxy acrylic resin, α-Al2O3 powder, and mica flake powder and mix well;
[0042] 3) grinding the obtained mixture to a slurry fineness of less than or equal to 30 microns;
[0043] 4) Cooling the ground slurry to below 35°C (including 35°C);
[0044] 5) Add latent cross-linking agent, stabilizer and wear-resistant agent and mix well.
[0045] In some embodiments, the resulting mixture is ground to a slurry fineness of less than or equal to 25 microns. In some embodiments, the resulting mixture is ground to a slurry fineness of less than or equal to 20 microns.
[0046] In the present invention, the hydroxy acrylic resin is an acrylic resin prepared by free radical polymerization reaction with hard monomers such as styrene or methyl methacrylate, soft monomers such as ethyl acrylate, butyl acrylate or butyl methacrylate, and hydroxyl-containing functional monomers such as hydroxyethyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate as raw materials under the action of a molecular chain regulator. The resin can be compounded with a crosslinking agent and cured to form a crosslinked network structure. The hydroxyl value of the hydroxy acrylic resin refers to the amount of hydroxyl group in 100g of the resin. The hydroxyl value usually used in industry refers to the milligrams of potassium hydroxide (KOH) equivalent to the hydroxyl groups in 1g of the sample, expressed in mg KOH / g.
[0047] In some embodiments, the hydroxy acrylic resin is a copolymer of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate. In some embodiments, the hydroxy value of the hydroxy acrylic resin is 40-60 mg KOH / g. In some embodiments, the hydroxy value of the hydroxy acrylic resin is 40-47 mg KOH / g. In some embodiments, the hydroxy value of the hydroxy acrylic resin is 47-53 mg KOH / g. In some embodiments, the hydroxy value of the hydroxy acrylic resin is 53-60 mg KOH / g. In some embodiments, the molecular weight of the hydroxy acrylic resin is 20000-30000. In some embodiments, the molecular weight of the hydroxy acrylic resin is about 25000.
[0048] The hydroxyl value and molecular weight of the hydroxy acrylic resin can be measured according to conventional methods in the art, or according to methods recommended by suppliers.
[0049] In the present invention, the cellulose acetate propionate is the product of esterification reaction between cellulose and propionic acid (anhydride) and acetic acid (anhydride). In some embodiments, the cellulose acetate propionate has an acetyl content of about 0.1-5%, a propionyl content of about 40-50%, and a hydroxyl content of about 0-5%.
[0050] In the present invention, the latent crosslinking agent refers to a compound that does not react with the polymer to be crosslinked or undergoes a balanced reversible crosslinking reaction under normal temperature and liquid conditions, but can rapidly undergo a crosslinking reaction with the polymer to be crosslinked after drying and heating. The latent crosslinking agent used in the present invention is selected from zirconate chelates, titanate chelates and any combination thereof. The latent crosslinking agent used in the present invention undergoes a crosslinking reaction with the hydroxyl-containing resin during the heating and drying process, so that the composition forms a coating.
[0051] The words "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different parts. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0052] The term "and / or" used in the present invention should be considered as a specific disclosure of each of two or more specified features or elements, as well as any combination of two or more features or elements. Therefore, the term "and / or" used in phrases, such as "A and / or B" herein, is intended to include "A and B", "A or B", "A" (alone) and "B" (alone).
[0053] The term "about" used in the present invention should be understood as within ±10%, ±9%, ±8%, ±7%, ±6%, ±5%, ±4%, ±3%, ±2%, ±1%, ±0.5%, ±0.1%, ±0.05% or ±0.01% of the specified value. Unless otherwise apparent from the context, all numerical values provided herein are modified by the term about. It should also be understood that the present invention discloses a number of numerical values, each of which should be understood to include the numerical value itself and the numerical value modified by "about". For example, the numerical value "10" represents the numerical value "10" itself and also represents "about 10". In any embodiment discussed in the context of a numerical value used in conjunction with the term "about", it is explicitly intended that the term about can be omitted.
[0054] Advantageous Effects of the Invention
[0055] The composition provided by the present invention can form an isolation coating on the surface of the label, enhance the structural rigidity of the label, balance the stress on both sides of the label substrate, and isolate the hot melt adhesive from the label substrate, thereby preventing the label from wrinkling and warping, ensuring the smooth and beautiful appearance of the label, and improving the packaging image of the product.
[0056] The label provided by the present invention is attached to the surface of the container without wrinkling or warping, and the label has a smooth and beautiful appearance, which can enhance the packaging image of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 It is a schematic diagram of the longitudinal cross-sectional structure of a hot melt adhesive labeling label coated with an isolation coating according to one embodiment of the present invention;
[0058] Figure 2 This is a picture showing the effect of a hot melt adhesive labeling label coated with an isolation coating in one embodiment of the present invention after being kept in an oven at 35° C. for one week;
[0059] Figure 3 This is a picture showing the effect of a hot melt adhesive labeling label coated with an isolation coating according to another embodiment of the present invention after being kept in an oven at 35° C. for one week. DETAILED DESCRIPTION
[0060] The substantive content of the present invention is further described below in conjunction with specific embodiments of the present invention. It should be understood that the following examples are only used to illustrate the present invention, but are not intended to limit the scope of protection of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to conventional conditions or manufacturer recommendations. The raw materials used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0061] Although many materials and operating methods used in the following examples are well known in the art, the present invention is still described in as much detail as possible. It is clear to those skilled in the art that the materials and operating methods used in the following examples are well known in the art unless otherwise specified.
[0062] The sources of various raw materials used in the embodiments of the present invention are as follows:
[0063]
[0064]
[0065] Example 1
[0066] The density of the printing substrate is 0.8g / cm 3 High-density double-sided corona pearlescent film with a corona value of 38 dynes.
[0067] Preparation of isolation coating:
[0068] The formulation of the barrier coating is:
[0069] Element Mass percentage Ethyl acetate 44.8% Cellulose Acetate Propionate 8% Hydroxylated acrylic resin (hydroxyl value 1.7%) 20% <![CDATA[α-Al2O3 powder (500-600 mesh)]]> 6% Mica flake powder (D50 particle size 5 microns) 7% Zirconate chelate (bis(diethylcitrate)dipropoxide zirconium(IV)) 3% Isopropyl alcohol 5% n-Propyl acetate 6% Polyethylene micronized wax 0.2% total 100%
[0070] Under the low-speed stirring mode of 500 rpm, slowly add cellulose acetate propionate solid powder to ethyl acetate. After all the powders are fed, the mixer is switched to high-speed (1000-1200 rpm) mode and stirred for more than 60 minutes until the cellulose acetate propionate solid powder is completely dissolved. Return to the low-speed mode, add hydroxyl acrylic resin (hydroxyl value is 1.7%) and stir evenly. Then add α-Al2O3 powder (500-600 mesh) and mica flake powder (D50 particle size 5 microns) while stirring. After all the powders are completely soaked in the liquid, switch the mixer to high-speed mode, stir and pre-disperse for 60 minutes before use. Finely grind the pre-dispersed slurry with a sand mill until the slurry fineness reaches less than 25 microns. After the ground slurry is left to cool to below 35°C, add 3% by mass zirconate chelate (bis(diethylcitrate)dipropoxide zirconium) as a latent crosslinking agent while stirring. Then, isopropyl alcohol is added as a stabilizer, n-propyl acetate is added to adjust the coating's suitable drying speed, and finally polyethylene micro-powder wax is added to adjust the coating's wear resistance.
[0071] The back of the double-sided corona pearlescent film is coated with an isolation coating by gravure coating, with a gravure line number of 65 lines / cm and a plate depth of 50 microns. The isolation coating is diluted with ethyl acetate to a viscosity test value of tea 3# cup 18 seconds later and then printed on the machine for coating, with a dry basis coating amount (i.e., the coating amount of the isolation coating after drying) of 1.6 g / m2, a drying temperature of 70 degrees Celsius, and a drying time of 2 seconds.
[0072] After the coating is completed, the label is tested and evaluated. The surface of the isolation coating is tested for adhesion strength using 3M600 tape and no coating is seen to fall off. The surface tension of the isolation coating is 68 dynes, which meets the requirements. Hot melt adhesive is applied to the back of the label for performance evaluation. Figure 2 As shown in the figure, the label was kept in a 35°C oven for one week without any obvious warping or wrinkling problems, which met the expected requirements.
[0073] Example 2
[0074] The density of the printing substrate is 0.65g / cm 3 Low density double-sided corona pearlescent film with a corona value of 38 dynes.
[0075] Preparation of isolation coating:
[0076] The formulation of the barrier coating is:
[0077] Element Mass percentage Ethyl acetate 38.5% Cellulose Acetate Propionate 10% Hydroxylated acrylic resin (hydroxyl value 1.8%) 18% <![CDATA[α-Al2O3 powder (500 - 600 mesh)]]> 10% Mica flake powder (D50 particle size 5 microns) 5% Titanate chelate (titanium acetylacetonate) 5% Isopropyl alcohol 7% n-Propyl acetate 5% Polyethylene micronized wax 1.5% total 100%
[0078] Under the low-speed stirring mode of 500 rpm, slowly add cellulose acetate propionate solid powder to ethyl acetate. After all the powders are fed, the mixer is switched to high-speed (1000-1200 rpm) mode and stirred for more than 60 minutes until the cellulose acetate propionate solid powder is completely dissolved. Return to the low-speed mode, add hydroxyl acrylic resin (hydroxyl value is 1.8%) and stir evenly. Then add α-Al2O3 powder (500-600 mesh) and mica flake powder (D50 particle size 5 microns) while stirring. After all the powders are completely soaked in the liquid, switch the mixer to high-speed mode, stir continuously for 60 minutes before pre-dispersion. Finely grind the pre-dispersed slurry with a sand mill until the slurry fineness reaches less than 25 microns. After the ground slurry is left to cool to below 35°C, add 5% by mass of titanate chelate (titanium acetylacetonate) as a latent crosslinking agent while stirring. Then, isopropyl alcohol is added as a stabilizer, n-propyl acetate is added to adjust the coating's suitable drying speed, and finally polyethylene micro-powder wax is added to adjust the coating's wear resistance.
[0079] The back of the double-sided corona pearlescent film is coated with a release coating by differential coating, and the release coating is diluted with n-propyl acetate to a viscosity test value of tea 3# cup, and then coated on a machine after 25 seconds, and the wet basis coating amount is controlled at 12 g / m2, the drying temperature is 80 degrees Celsius, and the drying time is 4 seconds. After drying, the coating amount of the release coating, that is, the dry basis coating amount, is about 2.2 g / m2.
[0080] After the coating is completed, the label is tested and evaluated. The surface of the isolation coating is tested for adhesion strength using 3M600 tape and no coating is seen to fall off. The surface tension of the isolation coating is 48 dynes, which meets the requirements. Hot melt adhesive is applied to the back of the label for performance evaluation. Figure 3 As shown in the figure, the label was kept in a 35°C oven for one week without any obvious warping or wrinkling problems, which met the expected requirements.
[0081] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art that various modifications and substitutions may be made to those details based on all the teachings disclosed, and these changes are within the scope of protection of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.
Claims
1. A composition for a label, comprising cellulose acetate propionate, hydroxy acrylic resin, α-Al2O3 powder, mica flake powder, a latent crosslinking agent, a stabilizer, an anti-wear agent and a first solvent, wherein the stabilizer is anhydrous ethanol or isopropanol, the anti-wear agent is micro-powdered polyethylene wax or micro-powdered polytetrafluoroethylene wax or a mixture of the two, and the first solvent is ethyl acetate and / or n-propyl acetate.
2. The composition of claim 1, which is composed of the following substances in percentage by mass:
3. The composition of claim 2, which is composed of the following substances in percentage by mass:
4. The composition of claim 3, which is composed of the following substances in percentage by mass:
5. The composition of claim 4, which is composed of the following substances in percentage by mass: It is composed of the following substances in terms of mass percentage:
6. The composition of any one of claims 1 to 5, wherein the latent crosslinking agent is selected from the group consisting of zirconate chelates, titanate chelates, and any combination thereof.
7. The composition of claim 6, wherein the latent crosslinking agent is selected from the group consisting of zirconium bis(diethyl citrate) dipropoxide, titanium acetylacetonate, and any combination thereof.
8. The composition of any one of claims 1 to 7, wherein the stabilizer is isopropyl alcohol.
9. The composition of any one of claims 1 to 8, wherein the first solvent is a combination of ethyl acetate and n-propyl acetate, Preferably, the mass ratio of ethyl acetate to n-propyl acetate is (3-15):1; Preferably, the mass ratio of ethyl acetate to n-propyl acetate is (5-10):1; Preferably, the mass ratio of ethyl acetate to n-propyl acetate is (7.5-8):1; Preferably, the α-Al2O3 powder is a powder of 500-600 mesh; Preferably, the D50 particle size of the mica flakes is 2-8 microns, preferably 5 microns; Preferably, the cellulose acetate propionate has an acetyl content of 0.1-5%, a propionyl content of 40-50%, and a hydroxyl content of 0-5%; Preferably, the cellulose acetate propionate has an acetyl content of about 2.5%, a propionyl content of about 45%, and a hydroxyl content of about 2.6%; Preferably, the molecular weight of the hydroxy acrylic resin is 20,000-30,000, such as about 25,000; Preferably, the hydroxyl value of the hydroxy acrylic resin is 40-60 mg KOH / g, such as 40-47 mg KOH / g, 47-53 mg KOH / g, 53-60 mg KOH / g, about 56 mg KOH / g; Preferably, the anti-wear agent is micronized polyethylene wax.
10. A coating formed by coating the composition according to any one of claims 1 to 9.
11. A method for preparing the coating of claim 10, comprising: 1) diluting the composition according to any one of claims 1 to 9 with a second solvent, 2) applying the diluted composition onto a substrate by gravure coating or differential coating, 3) Drying; Preferably, the second solvent is ethyl acetate and / or n-propyl acetate, preferably ethyl acetate; Preferably, after drying, the coating has a coating weight of 1.5-2.5 g / m 2 , for example about 1.6 g / m 2 , about 1.7g / m 2 , about 1.8g / m 2 , about 1.9g / m 2 , about 2.0g / m 2 , about 2.1g / m 2 , about 2.2g / m 2 , about 2.3g / m 2 , about 2.4g / m 2 ; Preferably, the drying is carried out at a temperature of 70-80°C for 2-5 seconds.
12. A label comprising a label substrate, a printing layer located on the front side of the label substrate, and a coating according to claim 10 located on the back side of the label substrate; Preferably, the printing layer includes an ink printing layer and a varnish printing layer; Preferably, the label substrate is a pearlescent film; Preferably, the label substrate is a double-sided corona pearlescent film. Preferably, the label substrate has a density of 0.65 to 0.8 g / cm 3 Pearlescent film; Preferably, the label substrate has a density of 0.65 to 0.8 g / cm 3 The double-sided corona pearlescent film has a corona value preferably greater than or equal to 38 dynes.
13. A packaging material comprising a container and the label of claim 12, wherein the label is attached to the surface of the container by hot melt adhesive; Preferably, the container is a bottle; Preferably, the container is made of one or more materials selected from high-density polyethylene, polyethylene terephthalate and polypropylene; Preferably, the hot melt adhesive is a rubber-based hot melt adhesive.
14. A method for preparing a composition according to any one of claims 1 to 9, comprising: 1) adding cellulose acetate propionate to a solvent to dissolve it; 2) Add hydroxy acrylic resin, α-Al2O3 powder, and mica flake powder and mix well; 3) grinding the obtained mixture to a slurry fineness of less than or equal to 30 microns, preferably less than or equal to 25 microns, and more preferably less than or equal to 20 microns; 4) Cooling the ground slurry to below 35°C (including 35°C); 5) Add latent cross-linking agent, stabilizer and wear-resistant agent and mix well.
Citation Information
Patent Citations
Adhesion promoting compounds for apolar substrates
CN111278931A
Composition for printing and high-resistance surface printing pearlized film label
CN118126570A
Liquid printing ink, printed matter, and packaging material
JP2020200441A
Varnish for heat shrinkable film, printed matter, and laminate
JP2023068791A
Decorative transfer label with ink-only layer
US20100065197A1